Immigration as risk factor for non-suicidal self-injury and suicide attempts in adolescents in Germany. Issue 1 (December 2015) - Plener, Paul; Munz, Lara; Allroggen, Marc; Kapusta, Nestor; Fegert, Jörg; Groschwitz, Rebecca
Abstract Background Whereas non-suicidal self-injury (NSSI) and suicide attempts (SA) are rather common among adolescents, the description of risk factors has often failed to take migration into perspective. Our study aimed to describe immigration status in adolescents with regards to their lifetime history of NSSI and SA. Methods We carried out a population based study in a school community of ninth-graders (N = 452, mean age 14.85, SD 0.58) in southern Germany. Data were collected via adolescent self report on sociodemographic variables and on NSSI and SA using the Self Harm Behavior Questionnaire. Results Adolescents born outside Germany showed an elevated rate of a lifetime history of NSSI and SA. When compared to German adolescents without a (family) history of migration (NSSI 19.16%, SA 3.24%), adolescents who were born in another country had an elevated risk for NSSI (42.86%, OR 3.36) and SA (17.86%, OR 6.78), which was higher than the risk of adolescents who had at least one parent who had emigrated from another country (NSSI 30.08%, OR 2.46 and SA 8.94%, OR 4.45). Conclusion Our findings should inform intervention services and prevention programs for NSSI and suicidality in youth. Adopting such programs to include culturally sensible modules could improve the outcome in ethnically diverse adolescents.